Penegakan Hukum Terhadap Praktik Prostitusi di Kota Bandung sebagai Penyakit Masyarakat Ditinjau dari Aspek Hukum Pidana dan Aspek Kriminologi - Regina Kanya Zulkafia; Dian Andriasari (Bandung Conference Series: Law Studies, 2023)
Abstract. Prostitution is an activity that involves at least two parties, including people who use sexual services and sexual service providers, also known as Commercial Sex Workers (PSK). The rise of the practice of prostitution in the city of Bandung is a question of how to enforce the law against the practice of prostitution. In the Criminal Code (KUHP) there are no specific provisions governing prostitution and which can ensnare users of Commercial Sex Worker services. Provisions in the Criminal Code can only be used to ensnare providers of Commercial Sex Work. This writing aims to find out how the law enforcement against the practice of prostitution in the city of Bandung as a disease of society and how the impact and obstacles in dealing with it. To find out and answer the analytical questions the author uses an empirical juridical approach. In the Criminal Code, provisions that are said to be related to prostitution are not imposed on prostitutes, while in Regional Regulations accountability sanctions are imposed on prostitutes. In enforcing regional regulations in the city of Bandung, one of them is carried out by the Civil Service Police Unit. Each in enforcing regional regulations has a legal basis. The general impacts that are considered worrying according to the community are of course related to comfort, embarrassment, and stigmatization. In contrast to the impact that is directly feared by the perpetrators of prostitution, in general they are afraid of the impact on matters relating to the joints of their lives. The obstacle experienced by the Civil Service Police Unit in Bandung City as the main actor in dealing with prostitution through regional apparatuses is public awareness. Apart from that, the implementation of regional regulations to deal with prostitution cannot be separated from the obstacles that arise in the form of disharmony between the community and law enforcement officials. Abstrak. Prostitusi merupakan suatu kegiatan yang melibatkan paling tidak dua orang pihak diantaraya ialah orang yang menggunakan jasa layanan seksual dan pemberi layanan seksual atau disebut sebagai Pekerja Seks Komersial (PSK). Maraknya praktik prostitusi di Kota Bandung menjadi pertanyaan bagaimana penegakan hukum terhadap praktik prostitusi. Dalam Kitab Undang-undang Hukum Pidana (KUHP) tidak ada ketentuan khusus yang mengatur mengenai prostitusi dan yang dapat menjerat pengguna jasa Pekerja Seks Komersial. Ketentuan dalam KUHP hanya dapat digunakan untuk menjerat penyedia Pekerja Seks Komersial. Penulisan ini bertujuan untuk mengetahui bagaimana penegakan hukum terhadap praktik prostitusi di Kota Bandung sebagai penyakit masyarakat serta bagaimana dampak serta hambatan dalam menanganinya. Untuk mengetahui dan mennjawab pertanyaan analisis tersebut penulis menggunakan metode pendeketan yuridis empiris. Dalam Kitab Undang-Undang Hukum Pidana, ketentuan-ketentuan yang dikatakan terkait dengan prostitusi tidak dijeratkan pada pelaku Prostitusi, sedangkan dalam Peraturan Daerah dijeratkan sanksi pertanggungjawaban bagi pelaku prostitusi. Dalam menegakan peraturan daerah di Kota Bandung salah satunya dilakukan oleh Satuan polisi Pamong Praja. Masing-masing dalam menegakan peraturan daerah memiliki dasar hukum. Dampak-dampak umum yang dirasa mengkhawatirkan menurut masyarakat tentunya berkenaan dengan kenyamanan, rasa malu, dan stigmatisasi. Berbeda dengan dampak yang dikhawatirkan langsung oleh para pelaku prostitusi, secara umum mereka takut akan dampak mengenai hal-hal yang berkaitan dengan sendi kehidupanya. Hambatan yang dialami Satuan Polisi Pamong Praja Kota Bandung sebagai pemeran utama dalam menangani prostitusi melalui perangkat daerah ialah kesadaran masyarakat. Selain itu dalam mewujudkan Peraturan Daerah untuk menangani prostitusi, tentunya tidak terlepas dari hambatan-hambatan yang timbul berupa adanya tidak keselerasan antara masyarakat dengan aparat penegak hukum.